Gestión de riesgos mayores para la Facultad de Ciencias Políticas y Administrativas de la Universidad Nacional de Chimborazo. - Quintanilla Godoy, Dennys Jhoel (2025)
The objective of this research was to develop a major risk management plan for the Faculty of Political and Administrative Sciences at the National University of Chimborazo (UNACH), in compliance with current legal regulations and with the aim of improving accident prevention and mitigation measures. To identify the risks, an on-site inspection was conducted in various areas of the building, evaluating the available resources using the FEMA matrices, MESERI, and the vulnerability matrix for institutions. The studied population included 1,424 users, corresponding to the maximum capacity of the Faculty of Political Sciences. The results revealed that the main threats to the faculty are earthquakes, floods, epidemics, pests, fires, explosions, gas leaks, poisonings, assaults, and civil unrest. The FEMA 154 analysis indicated a medium vulnerability, meaning that reinforcing the building's structure is not necessary. According to the fire risk assessment using the MESERI method, a medium risk was obtained with a value of 5.06. On the other hand, the vulnerability analysis for institutions showed risk levels ranging from low to medium for natural, technological, and human factors. Based on these results, an emergency plan was designed, which serves as an effective tool to improve response capacity in emergencies, protecting both people and property, as well as the environment.